Eicosanoids in the Innate Immune Response: TLR and Non-TLR Routes - Yolanda Alvarez; Isela Valera; Cristina Municio; Etzel Hugo; Francisco Padrón; Lydia Blanco; Mario Rodríguez; Nieves Fernández; Mariano Sánchez Crespo (Mediators of Inflammation)
The variable array of pattern receptor expression in different cells of the innate immune system explains the induction of distinct patterns of arachidonic acid (AA) metabolism. Peptidoglycan and mannan were strong stimuli in neutrophils, whereas the fungal extract zymosan was the most potent stimulus in monocyte-derived dendritic cells since it induced the production of PGE2, PGD2, and several cytokines including a robust IL-10 response. Zymosan activated κB-binding activity, but inhibition of NF-κB was associated with enhanced IL-10 production. In contrast, treatments acting on CREB (CRE binding protein), including PGE2, showed a direct correlation between CREB activation and IL-10 production. Therefore, in dendritic cells zymosan induces il10 transcription by a CRE-dependent mechanism that involves autocrine secretion of PGE2, thus unraveling a functional cooperation between eicosanoid production and cytokine production.